Tinjauan Filsafat Moral Utilitarianisme dan Deontologis dalam Serat Sestradi Kadipaten Pakualaman - Ryhan Aghani, Muhammad; Sabrina, Dinda (Humanis; Vol 29 No 1 (2025), 2025)
Serat Sestradi is a work by Kanjeng Gusti Paku Alam II, containing 21 behavioral guidelines that are regarded as valuable references for moral education in society. Based on the moral values presented in Serat Sestradi, this study aims to classify moral actions through the lens es of Utilitarianism and Deontological ethics. The research employs a qualitative-descriptive approach , utilizing library research, analyzing literature ,including   books and scholarly articles related to Serat Sestradi and ethical philosophy. The findings reveal that the moral values contained in the 21 guidelines can be classified within the framework s of both Utilitarian and Deontological ethics.